Isolation, Development, and Genomic Analysis of Bacillus megaterium SR7 for Growth and Metabolite Production Under Supercritical Carbon Dioxide - Freedman, Adam J. E.; Peet, Kyle C.; Boock, Jason T.; Penn, Kevin; Prather, Kristala L. J.; Thompson, Janelle R. (Frontiers in Microbiology, 2018)
Supercritical carbon dioxide (scCO2) is an attractive substitute for conventional organic solvents due to its unique transport and thermodynamic properties, its renewability and labile nature, and its high solubility for compounds such as alcohols, ketones and aldehydes. However, biological systems that use scCO2 are mainly limited to in vitro processes due to its strong inhibition of cell viability and growth. To solve this problem, we used a bioprospecting approach to isolate a microbial strain with the natural ability to grow while exposed to scCO2. Enrichment culture and serial passaging of deep subsurface fluids from the McElmo Dome scCO2 reservoir in aqueous media under scCO2 headspace enabled the isolation of spore-forming strain Bacillus megaterium SR7. Sequencing and analysis of the complete 5.51 Mbp genome and physiological characterization revealed the capacity for facultative anaerobic metabolism, including fermentative growth on a diverse range of organic substrates. Supplementation of growth medium with L-alanine for chemical induction of spore germination significantly improved growth frequencies and biomass accumulation under scCO2 headspace. Detection of endogenous fermentative compounds in cultures grown under scCO2 represents the first observation of bioproduct generation and accumulation under this condition. Culturing development and metabolic characterization of B. megaterium SR7 represent initial advancements in the effort towards enabling exploitation of scCO2 as a sustainable solvent for in vivo bioprocessing.